Obesity and Cancer: the Profile of a Population who Underwent Bariatric Surgery - Brito, H (2021)
Introduction Obesity is a significant risk factor for cancer incidence and mortality. The number of patients with obesity who undergo bariatric surgery is increasing; however, the impact of such a procedure in affecting the risk of cancer is not completely understood yet. Methods We conducted a retrospective unicentric cohort study to characterize the occurrence of cancer in patients who underwent bariatric surgery from January 2010 to December 2018. For cases of cancer identified after bariatric surgery, we performed a cancer-free survival analysis over time. We also performed a cross-sectional analysis of demographic and clinical characteristics at the time of surgery and compared patients with or without a cancer diagnosis. Results Of the 2578 patients who underwent bariatric surgery, 117 patients (4.5%) were diagnosed with a cancer. Fifty-nine cases were diagnosed before surgery, and the remaining 58 cases occurred after the bariatric procedure. The prevalence of cancer was more accentuated in women (4.9%) than among men (2.7%). Thyroid and breast cancer were the most frequent before and after bariatric surgery, respectively. On average, patients with cancer diagnosis were older (49.0 vs 43.3 years, p<0.001) and with a lower level of education (7.4 vs 8.6 school years, p=0.002). Conclusion Almost all the cases of cancer identified in this study were obesity-related cancers. Further prospective studies are needed to extend the current knowledge regarding the cancer risk profile of patients who undergo bariatric surgery.